2011
DOI: 10.1002/pon.1939
|View full text |Cite
|
Sign up to set email alerts
|

Does screening for distress efficiently uncover meetable unmet needs in cancer patients?

Abstract: Objectives: We evaluated screening for distress in terms of its ability to uncover unmet need for psychosocial services in cancer patients. Correlates of distress, need for services and met and unmet need for services were investigated.Methods: Immediately after cancer treatment (T1) and 2 months later (T2), 302 patients completed the Hopkins Symptom Checklist-25 (HSCL-25) and a single question assessing the need for services. All distressed patients (HSCL-25X39) and non-distressed patients endorsing a need fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
147
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(167 citation statements)
references
References 39 publications
19
147
0
1
Order By: Relevance
“…In the earlier mentioned Dutch study in 302 cancer patients, female patients and younger patients were at higher risk of having a high level of PD [28]. In another paper studying 2776 patients with cancer visiting a tertiary cancer center in Canada, significant gender differences were found; female patients reported depressive symptoms more frequently than male patients and were more likely to receive psychosocial support [19].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In the earlier mentioned Dutch study in 302 cancer patients, female patients and younger patients were at higher risk of having a high level of PD [28]. In another paper studying 2776 patients with cancer visiting a tertiary cancer center in Canada, significant gender differences were found; female patients reported depressive symptoms more frequently than male patients and were more likely to receive psychosocial support [19].…”
Section: Discussionmentioning
confidence: 92%
“…After two months, regardless of distress level, 10% of all screened patients reported an unmet need for intervention. The study showed that the need for an intervention was positively related to the level of distress [28]. In a study evaluating 361 referrals for psycho-oncological counseling, 20% of newly referred patients never attended counseling.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Screening is not necessarily useful, even if valid screening tools are used [13]. Patients who are correctly identified as highly distressed may still not get help, and even if psychological support is available for these patients, they may not accept it [3].…”
Section: Introductionmentioning
confidence: 99%
“…The prescription is also problematic as it takes for granted that "monitoring/screening" and "communication skills training" will improve the care of patients with cancer. This is far from self-evident (see, e.g., Merckaert et al, 2010;Moore et al, 2013;Ito et al, 2011;van Scheppingen et al, 2011;Salmon & Young, 2011;Salmon et al, 2015). When reading Meggiolaro et al's (2015) study, a series of papers published in The Lancet about a year ago come to mind.…”
mentioning
confidence: 99%